Prognostic role of bioelectrical impedance phase angle for critically ill patients: A systemic review and meta-analysis - Zheng, Wen-He; Zhao, Yi-He; Yao, Yan; Huang, Hui-Bin (Frontiers in Medicine, 2023)
We searched for relevant studies in PubMed, Embase, and the Cochrane database up to Jan 20, 2022. Meta-analyses were performed to determine the association between the baseline PA after admission with survival. We further conducted subgroup analyses and sensitivity analyses to explore the sources of heterogeneity. Results: We included 20 studies with 3,770 patients. Patients with low PA were associated with a significantly higher mortality risk than those with normal PA (OR 2.45, 95% CI 1.97-3.05, P<0.00001). Compared to survivors, non-survivors had lower PA values (MD 0.82°, 95% CI 0.66-0.98; P<0.00001). Similar results were also found when pooling studies reported regression analyses of PA as continuous (OR=0.64; 95% CI 0.52-0.79, P<0.00001) or categorical variable (OR=2.42; 95% CI 1.76-3.34; P<0.00001). These results were further confirmed in subgroup analyses and sensitivity analyses. Conclusions: Our results indicated that PA may be an important prognostic factor of survival in critically ill patients and can nicely complement the deficiencies of other severity scoring systems in the ICU setting.